Is there life after debt? Revolution in the age of financial capitalism - Ole Bjerg (Finance and Society, 2015)
What happens to classic Marxist notions of revolution, exploitation and class struggle under the premise that we live in the age of financial rather than industrial capitalism? In this essay I argue that the logic of finance is the main structuring principle of the circulation of value, capital, and money today. Accordingly, we should no longer just think of class struggle in terms of workers and capitalists but also in terms of debtors and creditors. In financial capitalism class is determined by one's position relative to the production of money. This also means that a contemporary idea of revolution is a matter of radical change in the way that money comes into being.
Keywords: 300; Capitalism; exploitation; debt; money; financialisation; revolution